Reproductive traits of the intertidal sea star Anasterias antarctica (Echinodermata: Asteroidea) from the Beagle Channel, Argentina - Fraysse, Cintia Pamela; Boy, Claudia Clementina; Pérez, Analía Fernanda (Marine Biology)
Sea stars display diverse reproduction strategies and development patterns. Anasterias antarctica (Lütken, 1857) is an oral-brooder species with a wide distribution that plays an essential role as a top predator in the Beagle Channel intertidal and sub-tidal communities. Eight seasonal samplings (February, May, August, and November) were carried out during 2017 and 2018 at Ensenada Zaratiegui Bay (54°51ʹ S; 68°29ʹ W). The main objective was to describe the reproductive cycle of A. antarctica, the second to compare reproductive traits between two intertidal levels, and the third to study the ontogeny of the latest stages of the brooded offspring. Unexpectedly, females displayed two consecutive annual reproductive cycles. One cycle corresponds to the production of a few large oocytes (oocytes IV: 1080.0 ± 27.92 µm) that will develop into a lecithotrophic larva, which will be brooded (Cycle I), and the other cycle produces many smaller oocytes (oocytes ii: 219.30 ± 12.59 µm) and co-occurs with the brooding period (Cycle II). In both sexes, differences in the duration of gametogenesis and, in females, also differential resource allocation patterns were observed between the high and low intertidal zones. High intertidal individuals showed a delay in the onset of gametogenesis and an extension of its duration. Also, in females, the leap in the gonad wet weight (GW) occurs in latter reproductive stages in the high intertidal individuals. Aborted eggs and abnormal metamorphic juveniles could serve as nutritional reserves for the brooded offspring. Although the viability of the second spawning is still to be confirmed, this result raises new hypotheses about the reproduction of the brooder and wide-distributed A. antarctica. Fil: Fraysse, Cintia Pamela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Boy, Claudia Clementina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina ...